Emerging markets portfolio creating a Latin American portfolio peruvian case study - Lizarzaburu, Edmundo. R. (2012)
The case study seeks to identify the most important issues encountered in developing a new portfolio in a Latin America country, exploring several alternatives which include not only stock and sovereign bonds but also more sophisticate products such as American Depositary Receipt (ADR) or Exchange Traded Fund (ETF) from emerging countries, and determine what are the risks involved in the process following not only Basil III standards, but also the local best practice recommend by the local regulators. The study at the beginning used historical information (normal distribution formulas) of several equities and bonds (n = 142) and then selected five Peruvian instruments (one of this involved at least 25 equities, N = 5, n = 30) and then other 30 (one of this include an ETF, N = 30, n = 55) in order to determine the best return and risk combination for an emerging market portfolio. Besides, the additional objective is to examine and introduce the reader in some statistics formulas used in finance and risk management. Senior management must evaluate the issues associated with the new portfolio and strategy developed.